Efficient Capturing of Polycyclic Aromatic Micropollutants From Water Using Physically Crosslinked DNA Nanoparticles - Atchimnaidu, Siriki; Thelu, Hari Veera Prasad; Perumal, Devanathan; Harikrishnan, Kaloor S.; Varghese, Reji (Frontiers in Chemistry, 2020)
Crafting of non-covalently (physically) cross-linked DNA nanoparticles through multivalent host-guest interaction between β-CD functionalized branched DNA nanostructures as the host and a star-shaped adamantyl-terminated 8-arm poly(ethylene glycol) polymer as the guest is reported. The most remarkable structural features of DNA nanoparticles include their excellent biocompatibility and the possibility of various non-covalent interactions with both hydrophobic and hydrophilic organic molecules. Potential of DNA nanoparticles for the rapid and efficient capture of various micropollutants typically present in water including carcinogens (hydrophobic micropollutants), organic dyes (hydrophilic) and pharmaceutical molecules (hydrophilic) is also demonstrated. The capture of micropollutants by DNA nanoparticles is attributed to the various non-covalent interactions between DNA nanoparticles and the micropollutants. Our results clearly suggest that DNA based nanomaterials would be an ideal candidate for the capturing and removal of both hydrophilic and hydrophobic micropollutants typically present in water.